A Novel Class of N‐Sulfonyl and N‐Sulfamoyl Noscapine Derivatives that Promote Mitotic Arrest in Cancer Cells. (12th November 2019) - Yong, Cassandra; Devine, Shane M.; Gao, Xuexin; Yan, Angelina; Callaghan, Richard; Capuano, Ben; Scammells, Peter J.
Abstract: Noscapine displays weak anticancer efficacy and numerous research efforts have attempted to generate more potent noscapine analogues. These modifications included the replacement of the N ‐methyl group in the 6′‐position with a range of substituents, where N ‐ethylcarbamoyl substitution was observed to possess enhanced anticancer activity. Herein, we describe advances in this area, namely the synthesis and pharmacological evaluation of a series of N ‐sulfonyl and N ‐sulfamoyl noscapine derivatives. A number of these sulfonyl‐containing noscapinoids demonstrated improved activities compared to noscapine. (( R )‐5‐(( S )‐4, 5‐Dimethoxy‐1, 3‐dihydroisobenzofuran‐1‐yl)‐4‐methoxy‐6‐((1‐methyl‐1 H ‐imidazol‐4‐yl)sulfonyl)‐5, 6, 7, 8‐tetrahydro[1, 3]dioxolo[4, 5‐ g ]isoquinoline) (14  q ) displayed sub‐micromolar activities of 560, 980, 271 and 443 nM against MCF‐7, PANC‐1, MDA‐MB‐435 and SK‐MEL‐5 cells, respectively. This antiproliferative effect was also maintained against drug‐resistant NCI/Adr RES cells despite high expression of the multidrug efflux pump, P‐glycoprotein. Abstract : Noscapine displays weak anticancer efficacy, and numerous research efforts have attempted to generate more potent noscapine analogues. Herein, we report the synthesis and pharmacological evaluation of a series of N ‐sulfonyl and N ‐sulfamoyl noscapine derivatives. A number of these sulfonyl‐containing noscapinoids demonstrated improved activities relative to noscapine. Compound 14  q displayed sub‐micromolar potency against MCF‐7, PANC‐1, MDA‐MB‐435 and SK‐MEL‐5 cells, and the antiproliferative effect was also maintained against drug‐resistant NCI/Adr RES cells despite high expression of the multidrug efflux pump, P‐glycoprotein.